2017
DOI: 10.20319/lijhls.2017.32.1523
|View full text |Cite
|
Sign up to set email alerts
|

Self-Confidence and Satisfaction Among Nursing Students With the Use of High Fidelity Simulation at Arab American University, Palestine

Abstract: High fidelity simulation practice has now become an important part of the education of nursing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
2
1
2
Order By: Relevance
“…On the one hand side of the current survey, the results showed no difference in the levels of satisfaction and self-con dence in simulation between students admitted after secondary school and LPN to RN students; on the other hand, the higher the year level of the students, the higher their self-con dence in simulation learning, which is congruent with the results reached by Salameh (2017). This can be explained by the duration of exposure to real clinical settings during the program courses prior to the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 84%
“…On the one hand side of the current survey, the results showed no difference in the levels of satisfaction and self-con dence in simulation between students admitted after secondary school and LPN to RN students; on the other hand, the higher the year level of the students, the higher their self-con dence in simulation learning, which is congruent with the results reached by Salameh (2017). This can be explained by the duration of exposure to real clinical settings during the program courses prior to the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 84%
“…The results of the current survey showed no difference in the levels of satisfaction and self-confidence in simulation between students admitted after secondary school and LPN to RN students. Also, the higher the year level of the students, the higher their self-confidence in simulation learning, which is congruent with the results reached by [21]. This can be explained by the duration of exposure to real clinical settings during the program courses prior to the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, the alternative was to conduct the different theoretical and clinical classes using simulation at the clinical laboratories at the university campus or remotely using online simulation modules. At the current survey, students' levels of satisfaction and self-confidence in simulation learning were both just above the midpoint of the scales' possible scores (3.1 and 3.0, out of 5, respectively), which is lower than the results reported by [11,[19][20][21].…”
Section: Discussioncontrasting
confidence: 77%
“…This study found that the proportion of satisfaction with simulation-based education and associated factors was 70.95% among the student population, which is lower than in studies conducted in other regions 13 - 15 . This difference might be due to differences in methodology, sociodemographic characteristics of participants and the technological gap between the countries.…”
Section: Discussioncontrasting
confidence: 78%